Solving Dengue Fever Model using Explicit Four-Step Multistep Method - Sanusi, Danish Daniel; Isa, Syahirbanun (Enhanced Knowledge in Sciences and Technology, 2025)
This research investigates the modelling of dengue fever transmission using an explicit four-step multistep method. In tropical areas, dengue fever is a severe disease spread by mosquitoes that can cause significant public health problems. This study combines factors including infection, recovery, and natural mortality rates to model suspected, infected, and recovered populations. The Runge-Kutta approach was used to identify the starting values before applying Adam’s Bashforth explicit four-step multistep method, which is renowned for its precision. Its accuracy and stability over the Bernoulli wavelet approach were shown via MATLAB (R2024B version) simulations. This strategy demonstrates the explicit multistep method’s capacity to comprehend intricate disease dynamics and guide public health initiatives.